Apprendre une langue, découvrir une culture : faire l'expérience d'un jeu social. Un exemple à l’école primaire, en visioconférence - Carole Le Hénaff (Recherches en Éducation)
Our paper examines, for the learning of a foreign language, how the consideration of the practice of linguistic and cultural experience, associated with an expert practice, can permit to better understand others, their language and their culture. We rely on a case study at primary school during a videoconferencing session, with French students who learn English, and English students who learn French, while both classes are simultaneously cooking pancakes. For our analysis, we refer to the theoretical framework of the Joint Action in Didactics (JATD), and to its associated epistemology of language, notably through the concepts of language game / form of life, and of social game. Our aim is to re-problematize how languages and cultures are learnt and transmitted, through joint actions, particularly in order to provide elements of a response to the question of the complex link between the learning of a language and the discovery of cultural practices at school.